, 10140; -, 100 . ..

" ", "" " ". .
18.03.2013

LiveJournal Vkontakte Facebook Twitter

1 2 3...4

x + 2x - 1 + x - 2x - 1 , 1 ≤ x ≤ 2.

_______________________________________________________

:

x + 2x - 1 + x - 2x - 1 = x - 1 + 2x - 1 + 1 + x - 1 - 2x - 1 + 1 =
(x - 1 + 1)2 + (x - 1 - 1)2 = |√x - 1 + 1| + |√x - 1 - 1|.

, "+". , 1 ≤ x ≤ 2, x - 1 ≤ 1, "-".

|√x - 1 + 1| + |√x - 1 - 1| = √x - 1 + 1 + 1 - √x - 1 = 2.

: 2.


2x + 2x2 - y2 , xy > 0.

_____________________________________________

:

2x + 2x2 - y2 = x + y + 2x2 - y2 + x - y = (√x + y + √x - y)2 =
x + y + √x - y

: √x + y + √x - y.


10x + 225x2 - y2 - 10x - 225x2 - y2.

____________________________________________________

:

10x + 225x2 - y2 - 10x - 225x2 - y2 =
5x + y + 225x2 - y2 + 5x - y - 5x + y - 225x2 - y2 + 5x - y =
(√5x + y + √5x - y)2 - (√5x + y - √5x - y)2 = |√5x + y + √5x - y| - |√5x + y - √5x - y|.

, "+". . , 5x + y ≥ 0; 5x - y ≥ 0;

5x + y ≥ √5x - y 5x + y ≥ 5x - y, y ≥ 0.

5x + y < √5x - y, y < 0.

, y ≥ 0 "+":

|√5x + y + √5x - y| - |√5x + y - √5x - y| = √5x + y + √5x - y - √5x + y + √5x - y = 2√5x - y.

y < 0, "-":

|√5x + y + √5x - y| - |√5x + y - √5x - y| = √5x + y + √5x - y + √5x + y - √5x - y = 2√5x + y.

: y ≥ 0, 2√5x - y; y < 0, 2√5x + y.


1 2 3...4
2009-2012 . " - !" - , . .
Rambler's Top100